Effects of Different Forms and Doses of Sulphur Application on Wheat - Halil Erdem; Mustafa Bülent Torun; Nazife Erdem; Atilla Yazıcı; İnci Tolay; Elif Günal; Faruk Özkutlu (Turkish Journal of Agriculture: Food Science and Technology)
Deficiency of sulphur (S) is an important limiting factor of plant growth for sustainable agricultural production. The decline in sulphur dioxide emission, decrease in S-containing fertilizer consumption due to the high cost of S-fertilizers, breeding of new high yielding species are the well known causes of S-deficiency. A greenhouse experiment was conducted to investigate the effects of several doses of K2SO4-S, CaSO4-S and elemental-S applied on growth, shoot dry matter yield, S and N concentrations of wheat cultivar. The experiments were conducted in three soils differed from available S concentrations. Effects of different S-treatments (0, 25, 50 and 100 mg S kg-1) and S-forms had significant effects on shoot dry matter yields of plants. Sulphur from different S-sources did not increase shoot S-concentrations in Eskisehir and Konya soils, but increase was significant obtained in the Harran soil. Shoot S-concentration in Harran soil for zero K2SO4 treatment was 0.09%, the values were 0.22, 0.26 and 0.27% respectively for 25, 50 and 100 mg kg-1 treatments. The results indicated significant effects of S-treatments on plant growth and yield mostly based on soil properties, especially the available S-levels